Enhancing Patient–Provider Breastfeeding Conversations: Breastfeeding Intention and Prenatal Breastfeeding Self-Efficacy among a Sample of Pregnant Women. Issue 4 (April 2021) - McKinley, Erin M.; Knol, Linda L.; Turner, Lori W.; Burnham, Joy J.; Graettinger, Kristine R.; Hernandez-Reif, Maria; Leeper, James D.
Abstract: Objectives: The purpose of this study was to investigate and identify which sociodemographic factors may be associated with breastfeeding intention and breastfeeding self-efficacy among pregnant women. Methods: Pregnant women at a medical center in Alabama completed a cross-sectional survey. The Prenatal Rating of Efficacy in Preparation to Breastfeed Scale (PREP to BF) was used to assess prenatal breastfeeding self-efficacy. A valid 3-item breastfeeding intention scale and the Fetal Health Locus of Control Scale also were used. Nonparametric tests were used to assess differences in breastfeeding intention, locus of control subscales, and PREP to BF scores by history with breastfeeding, planned mode of delivery, and sociodemographic factors. Results: The participants in the final analysis ( N = 124) had a mean prenatal breastfeeding self-efficacy score of 299.5 (±92.33), with a range of 0 to 390. Significantly lower scores related to intention and PREP to BF were found among Black women ( P ⩽ 0.05), those with a high school education or less ( P ⩽ 0.019), single women ( P ⩽ 0.028), and those who had no breastfeeding experience ( P ⩽ 0.035). Conclusions: Identifying pregnant women with low breastfeeding self-efficacy and intention and recognizing the effects of social and cultural influences on breastfeeding are vital. Healthcare providers can engage in meaningful dialog to address ways to increase social support, communication, goal-setting skills, and overcoming mental and emotional barriers. Abstract : Identifying pregnant women with low breastfeeding self-efficacy and intention and recognizing the effects of social and cultural influences on breastfeeding may be the key to success in engaging in related conversations. Healthcare providers can engage in meaningful dialog to address ways to increase social support, communication, goal-setting skills, and overcoming mental and emotional barriers. These topics brought up in regular discussions at prenatal appointments may increase prenatal breastfeeding self-efficacy and influence actual initiation and duration of breastfeeding after birth. Providers also may address any cultural and social aspects that may be influencing low intention and prenatal breastfeeding self-efficacy.